2009
DOI: 10.1021/es900578v
|View full text |Cite
|
Sign up to set email alerts
|

Odd Isotope Deficits in Atmospheric Hg Measured in Lichens

Abstract: Redox reactions govern mercury (Hg) concentrations in the atmosphere because fluxes (emissions and deposition), and residence times, are largely controlled by Hg speciation. Recent work on aquatic Hg photoreduction suggested that this reaction produces non-mass dependent fractionation (NMF) and that residual aquatic Hg(II)is characterized by positive delta199Hg and delta201Hg anomalies. Here, we show that atmospheric Hg accumulated in lichens is characterized by NMF with negative delta199Hg and delta201Hg valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
114
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 38 publications
16
114
3
4
Order By: Relevance
“…The vertical bars represent the estimated crust-and mantel-derived Hg. [229], Gosh et al [230], Carignan et al [234], Bergquist et al [191].…”
Section: Mercury Isotopesmentioning
confidence: 99%
“…The vertical bars represent the estimated crust-and mantel-derived Hg. [229], Gosh et al [230], Carignan et al [234], Bergquist et al [191].…”
Section: Mercury Isotopesmentioning
confidence: 99%
“…Fractionation of Hg has been detected in a large variety of environmental compartments, e.g. hydrothermal Hg-bearing ores [8][9][10], coals [11,12], soil/sediments [7,[13][14][15], atmospheric Hg [16] and biological tissues [17]. Above cited studies have unequivocally demonstrated that variations in the Hg isotopic signature could be used in the future as tracers to distinguish between Hg sources and important chemical transformation processes in the environment.…”
mentioning
confidence: 99%
“…[16,29], Hg entering the environment through varies industrial activities probably have little to no MIF signatures. However, large variation of MIF was observed in the sub-surface environment compartments such as in aquatic systems [17] and atmospheres [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations